Counterpoint and Non-harmonic tone Arrangements on “Bungong Jeumpa” Song Arrangements Works of Paul Widyawan - Jagar Lumbantoruan (Universitas Negeri Medan, 2023)
The purpose of this study is to analyze and describe Paul Widyawan's “Bungong Jeumpa” song about conterpoint and non-harmonic tone arrangements. This type of research is qualitative with a content analysis approach, namely: objectivity, systematic, and generalization. The data in this study were taken from literature studies and song scores. The analysis technique uses choral composition techniques, conterpoint, and non-harmonic tones. The results showed that the composition of “Bungong Jeumpa”'s song has three parts, namely: intro, content, and coda. The intro consists of 8 measure chambers, contains 20-measure chambers, and 4 coda chambers. The arrangement of the song is a polyphony-homophony texture, based on the Cantus Firmus. SATB's melodic contour relationships are tonal conterpoint in the key of A minor harmonics. Each melodic contour moves with the same rhythm and is generally different. Differences in melodic contours produce four types of Motus, namely parallellus, contrarius, obliqus, and rectus. Besides that, with the differences in the rhythm and melody of the songs on SATB with the presence of insert notes between the harmonic tones, there is also a different musical atmosphere. Based on position, motion, and solutions of dissonant tones, five types were found, namely: passing tone, appoggiatura, changing tone, neighbouring tone, and retardation.